Seed-Specific Expression of a Feedback-Insensitive Form of CYSTATHIONINE-γ-SYNTHASE in Arabidopsis Stimulates Metabolic and Transcriptomic Responses Associated with Desiccation Stress . Issue 3 (17th September 2014) - Cohen, Hagai; Israeli, Hadasa; Matityahu, Ifat; Amir, Rachel
Abstract : Methionine metabolism in Arabidopsis seeds is strongly associated with stress-related metabolites and transcripts, suggesting that its content leads to desiccation stress during seed development . Abstract: With an aim to elucidate novel metabolic and transcriptional interactions associated with methionine (Met) metabolism in seeds, we have produced transgenic Arabidopsis ( Arabidopsis thaliana ) seeds expressing a feedback-insensitive form of CYSTATHIONINE-γ-SYNTHASE, a key enzyme of Met synthesis. Metabolic profiling of these seeds revealed that, in addition to higher levels of Met, the levels of many other amino acids were elevated. The most pronounced changes were the higher levels of stress-related amino acids (isoleucine, leucine, valine, and proline), sugars, intermediates of the tricarboxylic acid cycle, and polyamines and lower levels of polyols, cysteine, and glutathione. These changes reflect stress responses and an altered mitochondrial energy metabolism. The transgenic seeds also had higher contents of total proteins and starch but lower water contents. In accordance with the metabolic profiles, microarray analysis identified a strong induction of genes involved in defense mechanisms against osmotic and drought conditions, including those mediated by the signaling cascades of ethylene and abscisic acid. These changes imply that stronger desiccation processes occur during seed development. The expression levels of transcripts controlling the levels of Met, sugars, and tricarboxylic acid cycle metabolites were also significantly elevated. Germination assays showed that the transgenic seeds had higher germination rates under salt and osmotic stresses and in the presence of ethylene substrate and abscisic acid. However, under oxidative conditions, the transgenic seeds displayed much lower germination rates. Altogether, the data provide new insights on the factors regulating Met metabolism in Arabidopsis seeds and on the mechanisms by which elevated Met levels affect seed composition and behavior.